Separation of goat milk to whey protein by cross flow filtration using hollow fibre membrane - Arumugam, Gayathri (2010)
Separation of whey protein in goat milk by cross flow filtration using hollow fibre membrane is a good way for protein purification Cross flow filtration is a good protein purification method because it can operate continuously and does not require frequent maintenance therefore can be applied for industrial use . Protein separation by microfiltration requires pretreatment which includes centrifugation and filtration using Whatman filter paper to remove fat layer . Casein precipitation is done by reducing pH of goat milk to 4.6 to avoid fouling la yer on membrane . Microfiltration is rim using whey solution of varying pH and cross flow velocity to stud y concentration of whey protein in permeate during cross flow filtration . Whey protein concentration in sample collected froth permeate is analysed using Reverse Phase Chromatograpy RPC) where peak obtained is compared with standard to determine whey concentration . pH values selected is from range 6 to 8 and cross flow velocity range from 0.01 cm/s to 0.03 cm/s .. Concentration of whey protein B SA and f - lactoglobulin shows highest value compared to other pH values . pH 6.5 was an optimum pH because .wheyprotein gets denatured at higher pH and gets precipitated at lower pH . Concentration of whey protein is highest at cross flow velocity value of 0.03 cm/s . Whe y protein concentration increases steadilyas cross flow velocity increases . Cross flow filtration is an efficient method for protein purification and can be applied in industry.